ANALISIS NILAI PELANGGAN TERHADAP KEPUASAN DAN LOYALITAS (Studi Kasus Pada BMT Cengkareng) - Syarifuddin Hasan (Universitas Sebelas Maret, 2014)
This article exposed how customer get value customer in terms of adequated and desired services. For this purpose, the study used SEM method in order to show up the direct relationship among value customer and loyality.Result of the study indicated that customer value has high significant influenced to desired services, but it has negative influenced to loyality. It means that customer loyality will be decrease if their expectation and perception of satisfaction is too high. Meanwhile, the study pointed out that positive and significant influence of adequated services to loyallity. So, whenever adequated services goes up it will increase customer loyality as well.